Indications of surface-dominated transport in single crystalline nanoflake devices of topological insulator Bi_{1.5}Sb_{0.5}Te_{1.8}Se_{1.2} - Xia, Bin (2013)
We report experimental evidence of surface-dominated transport in single crystalline nanoflake devices of topological insulator Bi1.5Sb0.5Te1.8Se1.2 (BSTS). The resistivity measurements show dramatic differences between the nanoflake devices and bulk single crystal. Based on a two-channel model, the analysis on the resistivity and Hall resistance indicates that ∼99% surface transport contribution can be realized in 200 nm-thick BSTS nanoflake devices. Using a standard back gate with SiO2 as a dielectric layer, a pronounced ambipolar electric field effect was observed in devices fabricated with 100–200 nm thick flakes.Moreover, angle-dependent magnetoresistances of a nanoflake device with a thickness of 596 nanometers are fitted to a universal curve for the perpendicular component of the applied magnetic field. The value of phase coherence length obtained from two-dimensional weak antilocalization fitting further confirmed the surface dominated transport. Our results open a path for realization of electric and spintronic devices based on the topological helical surface states.